2020
DOI: 10.1371/journal.ppat.1009018
|View full text |Cite
|
Sign up to set email alerts
|

Defensin-driven viral evolution

Abstract: Enteric alpha-defensins are potent effectors of innate immunity that are abundantly expressed in the small intestine. Certain enteric bacteria and viruses are resistant to defensins and even appropriate them to enhance infection despite neutralization of closely related microbes. We therefore hypothesized that defensins impose selective pressure during fecal-oral transmission. Upon passaging a defensin-sensitive serotype of adenovirus in the presence of a human defensin, mutations in the major capsid protein h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Wild-type Ad5 was obtained from ATCC and recombinant adenovirus vectors rAd VII-GFP and rAd GFP were a gift from D. Curiel [ 72 ]. Ad5 VII-HA was generated using bacterial recombineering with an E3-deleted Ad5 bacterial artificial chromosome (BAC) vector [ 73 , 74 ]. Briefly, an HA tag was added to the protein VII gene through PCR amplification, and then protein VII was introduced into the Ad5 genome through recombineering.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type Ad5 was obtained from ATCC and recombinant adenovirus vectors rAd VII-GFP and rAd GFP were a gift from D. Curiel [ 72 ]. Ad5 VII-HA was generated using bacterial recombineering with an E3-deleted Ad5 bacterial artificial chromosome (BAC) vector [ 73 , 74 ]. Briefly, an HA tag was added to the protein VII gene through PCR amplification, and then protein VII was introduced into the Ad5 genome through recombineering.…”
Section: Methodsmentioning
confidence: 99%
“…we created an α-defensin-resistant HAdV-B-based vector expressing eGFP following the principles of Diaz et al [8]. We substituted sequences in three capsid proteins of HAdV-B35 (fiber, hexon, and penton base) with the corresponding amino acids of HAdV-D37 (Fig 6A ), which like HAdV-D64 is an EKC-causing virus that is naturally resistant to HD5 and HNP1 [10].…”
Section: Defensin-dependent Binding Expands the Cellular Tropism Of H...mentioning
confidence: 99%
“…Although the antimicrobial activities of defensins have been investigated most extensively, particular types of human adenovirus (HAdV), adeno-associated virus (AAV), mouse adenovirus (MAdV), rotavirus, and human immunodeficiency virus have been shown to be either resistant to α-defensin neutralization or even able to commandeer α-defensins to enhance their infection [6][7][8][9][10][11][12][13]. Similarly, infection by the bacterial pathogen Shigella is increased by α-defensins, and some commensal bacterial species are resistant to α-defensin killing [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In HAdV-F41 and HAdV-D26, HVR1 is shorter than in HAdV-C5 and could be fully traced in cryo-EM maps [ 29 , 30 ]. The acidic HVR-1 in HAdV-C5 seems to be involved in electrostatic interactions with neutralizing defensins, and its absence in species D and F may play a role in determining the enteric or ocular tropism of these viruses, although this aspect is not well understood yet [ 30 , 49 ]. In lizard adenovirus type 2 (LAdV-2), an Atadenovirus, the loops are shorter and could be modeled without gaps.…”
Section: Structure Of the Capsid Proteinsmentioning
confidence: 99%
“…Nevertheless, it has been recently shown that HAdV-F41 binds laminin-binding integrins [ 53 ]. Since the RGD loop is also involved in neutralization by the enteric defensin HD5, it has been proposed that lack of both this sequence motif and the acidic HVR1 in hexon may play a role in facilitating infection of intestinal cells by HAdV-F40 and HAdV-F41 [ 30 , 49 ]. Another surface-exposed variable loop presents sequence divergence and different conformations in the human adenoviruses [ 7 , 29 , 30 , 51 ].…”
Section: Structure Of the Capsid Proteinsmentioning
confidence: 99%